SEMINAR RESCHEDULED AND REQUEST FOR VENTILATION STUDY AS A PRELIMINARY STEP IN DEVELOPING A SMOKING POLICY (Tufts Archival Research Center, 2007)
MARGINALIA; Letter from Susan Stuntz to Gray Robertson regarding an indoor air quality seminar for AFL-CIO OSHA directors. Requests that an analysis of air quality be performed for the American Federation of Government Employees (AFGE) at the cost of the labor management committee.